Developing Learning Material for Writing Descriptive Essays Assisted by an Animated Video - Hoesny, Mariana Ulfah; Peruzzi, Erico; Budianto, Aris (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study developed writing materials and animated videos to improve students’ essay writing at the State Polytechnic of Malang. Following Richey and Klein’s five-phase Design and Development Research model, analysis through questionnaires and interviews identified grammar difficulties and low motivation as major writing challenges. To address these, the researcher created a module with reading passages, grammar sections, and QR-linked animated videos. The final product was field-tested with students, yielding positive feedback (some noted video pacing issues). The final product scored 72.43% in the evaluation, confirming its effectiveness in supporting essay writing. Students appreciated the engaging visuals, clear explanations, and bilingual format. Integrating animation into traditional writing materials enhanced student understanding and motivation. This module and video series serve as a practical, innovative instructional tool. Future work should improve video pacing and add interactive learning features.